Precision measurement of CP violation in the penguin-mediated decay B0s → ϕϕ - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kubat, Jakub; Leverington, Blake; Marks, Jörg; et al. (Physical review letters, 2023)
A flavor-tagged time-dependent angular analysis of the decay 𝐵0𝑠→𝜙⁢𝜙 is performed using 𝑝⁢𝑝 collision data collected by the LHCb experiment at the center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 6 fb−1. The 𝐶⁢𝑃-violating phase and direct 𝐶⁢𝑃-violation parameter are measured to be 𝜙𝑠⁢¯𝑠⁢𝑠𝑠=−0.042±0.075±0.009 rad and |𝜆|=1.004±0.030±0.009, respectively, assuming the same values for all polarization states of the 𝜙⁢𝜙 system. In these results, the first uncertainties are statistical and the second systematic. These parameters are also determined separately for each polarization state, showing no evidence for polarization dependence. The results are combined with previous LHCb measurements using 𝑝⁢𝑝 collisions at center-of-mass energies of 7 and 8 TeV, yielding 𝜙𝑠⁢¯𝑠⁢𝑠𝑠=−0.074±0.069 rad and |𝜆|=1.009±0.030. This is the most precise study of time-dependent 𝐶⁢𝑃 violation in a penguin-dominated 𝐵 meson decay. The results are consistent with 𝐶⁢𝑃 symmetry and with the standard model predictions.